Protein profiles of Streptomyces aureofaciens producing tetracyclines: reappraisal of the effect of benzyl thiocyanate - Novotná, J; Li, X M; Novotná, J; Vohradský, J; Weiser, J (Current microbiology, 1995)
Cell protein profiles of submerged cultures of Streptomyces aureofaciens cultivated in the absence or presence of 12 microM benzyl thiocyanate (BT) were analyzed by one-dimensional SDS polyacrylamide gel electrophoresis. Substantial increase in the intensity of the 13, 35, 37, 60, and 100 kDa protein bands was observed in cultures treated with BT. Similar increase in the 35, 37, and 60 kDa bands was found in a mutant blocked in the last chlortetracycline biosynthesis step. Effect of BT on the solid medium-grown cultures was also observed, with a more intensive substrate mycelium pigmentation and alteration in the spore size and shape as the most characteristic features. Earlier studies of BT effect involving those on the stimulation of chlortetracycline biosynthesis are summarized and a possible signal-transducing mechanism is discussed from the point of view of adaptation of S. aureofaciens to the uncoupling of oxidative phosphorylation.
Keywords: tetracykliny; bakteriální proteiny; elektronová mikroskopie; Tetracyclines; Thiocyanates; Bacterial Proteins; thiokyanatany; Streptomyces aureofaciens; Microscopy, Electron